Presence and Molecular Characterization of Alfalfa mosaic virus on Tobacco in Serbia - Ivana Stanković; Ana Vučurović; Aleksandra Bulajić; Danijela Ristić; Janoš Berenji; Branka Krstić (Pesticidi i Fitomedicina, 2011)
Three-year investigation of the presence and distribution of tobacco viruses in Serbia revealed that Alfalfa mosaic virus (AMV) appeared every year with different frequency in tobacco crops. During 2008, the presence of AMV was detected in most of the tested samples(58.82%) and it was the second most common compared to all other viruses which presence was confirmed in Serbia. In 2006 and 2007, AMV was detected in a significantly lower percentage (2.80% and 13.64%, respectively). This study showed that Alfalfa mosaic virus was more commonly found in multiple infections with two, three or even four detected viruses. Single infections were detected only in 2006, in one tobacco field in the locality of Futog. During this investigation, a rapid and simple protocol was optimized and developed for molecular detection of AMV in tobacco leaves, using primers CPAMV1/CPAMV2 and commercially available kits for total RNA extraction as well as for RT-PCR (reverse transcription - polymerase chain reaction). Using RT-PCR and these primers that flank the AMV coat protein gene, a DNA fragment of 751 bp was amplified, sequenced, and compared with the sequences available in GenBank database. The sequence of isolate 196-08 (GenBank Acc. No. FJ527749) proved to be identical at the nucleotide level of 99 to 93% withthose from other parts of the world. Phylogenetic analysis of 27 isolates based on 528 bp sequences of the coat protein gene did not show correlation of the isolates with their geographic origin or plant host and showed that these isolates fall into four molecular groups of strains. Serbian AMV isolate from tobacco belongs to group IV, the group that includes most of the isolates selected for phylogenetic analysis.